Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/nature11525
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional thyroid from embryonic stem cells

Abstract: The primary function of thyroid gland is to metabolize iodide by synthesizing thyroid hormones that are critical regulators of growth, development and metabolism in virtually all tissues. To date, research on thyroid morphogenesis was missing an efficient stem-cell model system which allows to recapitulate in vitro the molecular and morphogenic events regulating thyroid follicular cells differentiation and subsequent assembly into functional thyroid follicles. Here we report that a transient overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
285
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(299 citation statements)
references
References 34 publications
(37 reference statements)
3
285
0
1
Order By: Relevance
“…4,19,20 A number of different methods for EB formation and differentiation exist, with recent improvements in controlled EB formation and maintenance of uniform sizes achieved by microtechnologies alone or in combination with hydrodynamic culture systems. 13,21,22 Regardless of the specific methods used, EBs generally exhibit a similar loss of pluripotent markers before progressive expression of differentiated phenotypes is observed.…”
Section: Discussionmentioning
confidence: 99%
“…4,19,20 A number of different methods for EB formation and differentiation exist, with recent improvements in controlled EB formation and maintenance of uniform sizes achieved by microtechnologies alone or in combination with hydrodynamic culture systems. 13,21,22 Regardless of the specific methods used, EBs generally exhibit a similar loss of pluripotent markers before progressive expression of differentiated phenotypes is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Most remarkably, it was recently demonstrated that pluripotent stem cells retain a self-organising ability to differentiate into 3D organoids, which resemble optic cups [142,143] and adenohypophysis tissues [144]. Similarly, intestinal organoids have been reported to develop from hESC-derived posterior endoderm monolayers upon exposure to the appropriate signalling factors [145], and functional thyroid gland tissue has been generated from mESCs [146]. Therefore, if one were to harness this powerful self-developing property of pluripotent stem cells for the generation of novel complex organ types for research or medical purposes, it would be important to first determine the mechanisms underlying these processes.…”
Section: Future Outlookmentioning
confidence: 99%
“…After treatment with TSH, these cells showed molecular, morphological and functional characteristics of thyroid follicles and were able to fulfil thyroid hormone deficits when transplanted orthotopically into an immunodeficient mouse. 33 Pax-8 and TTF-1 co-expression is therefore required for assembling the follicular cells into becoming a follicle-like structure, as recently confirmed. 38 Longmire et al demonstrated that the presence of activin A led ESCs to differentiate into definitive endoderm, expressing forkhead box protein A2 (Foxa2 + ).…”
Section: Normal Thyroid Stem Cellsmentioning
confidence: 60%
“…31,32 As discussed below, the co-expression of TTF-1 and Pax-8, is an essential event for cell commitment towards follicular cell fate. 33 While, FGF and bone morphogenetic protein (BMP) signalling pathways act in the early stages of thyroid development 34 before TSH/TSH-R and IGF/insulin signalling that promote the full differentiation of follicular cells ( Figure 4 and Table 1). 35 In order to identify early and late markers of thyroid development, several studies are being carried out using mouse ESCs as a source of in vitro differentiating thyrocytes.…”
Section: Normal Thyroid Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation